2001
DOI: 10.1002/cm.10004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of dynein and motility of a giant sperm axoneme provided with only the outer dynein arm

Abstract: The peculiar sperm axoneme of the dipteran Asphondylia ruebsaameni is characterized by an extraordinarily high number of microtubule doublets (up to 2,500) arranged in double parallel spirals. Doublets of the inner row of each spiral are tilted, so that their outer arms point towards the B-tubule of the next doublet in the outer row. Doublets are provided with only the outer arm, and no structure related to the central pair/radial spoke complex is present. When analyzed by quick-freeze, deep-etch electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…Despite missing the inner dynein arms, these spermatozoa are motile. Case studies of the Cecidomyiinaeans Monarthropalpus flavus (Schrank) (Lupetti et al , 1998) and Asphondylia ruebsaameni Kertesz (Mencarelli et al , 2001) revealed that spermatozoa stored within the male genital tract are folded into several turns. Folded spermatozoa are exhibiting a continuous train of bends running along the flagellum.…”
Section: Patterns Of Insect Sperm Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite missing the inner dynein arms, these spermatozoa are motile. Case studies of the Cecidomyiinaeans Monarthropalpus flavus (Schrank) (Lupetti et al , 1998) and Asphondylia ruebsaameni Kertesz (Mencarelli et al , 2001) revealed that spermatozoa stored within the male genital tract are folded into several turns. Folded spermatozoa are exhibiting a continuous train of bends running along the flagellum.…”
Section: Patterns Of Insect Sperm Motilitymentioning
confidence: 99%
“…In normal flagella, the ability to generate regular flagellar bending resides with the central complex and the inner dynein arms which are crucial in the regulation and coordination of dynein function (Gardner et al , 1994). In the case of Monarthropalpus flavus and Asphondylia ruebsaameni spermatozoa it was suggested that dynein function is regulated by external mechanical stimuli which compensate for the lack of inner dynein arms (Lupetti et al 1998, Mencarelli et al , 2001). This is also true for insect spermatozoa with the conventional axoneme structure (see Section V.).…”
Section: Patterns Of Insect Sperm Motilitymentioning
confidence: 99%
“…This hydrolysis is being carried out by dyenin ATPase which is an Mg 2+ ‐dependent enzyme localized on the axoneme (Gibbons & Gibbons, ). The importance of these dyenin arms in motility has clearly been established in several experiments showing a direct correlation between the quantity of dyenin arms present on the axoneme and the sliding velocity (Mencarelli et al ., ). In this study, Mg 2+ ‐dependent ATPase activity decreased from 1580 ± 2.0 units in control to 1020 ± 0.53 ( p < 0.01) units upon incubation with anti‐SR antibodies.…”
Section: Discussionmentioning
confidence: 97%
“…2). From the 3 + 0 structure in the parasitic protozoan Diplauxis hatti to the giant axoneme of the dipteran Asphondylia ruebsaameni with 2,500 microtubule doublets (Mencarelli et al 2001), variations are rich.…”
Section: Sperm Morphology and Ultrastructure Is Diversementioning
confidence: 99%